Numerical Investigation for Deterministic Hepatitis B Model using Adomian Decomposition Method - Muhammad Rifki Nisardi; Muh. Nursyam Siduppa; A. Ika Putriani; Nur Rahmi (Rangkiang Mathematics Journal, 2026)
Numerical solutions are an essential approach to addressing dynamical system problems involving differential equations. This study focuses on solving a modified SITR model for the spread of Hepatitis B using the Adomian Decomposition Method (ADM) to obtain numerical solutions. The advantage of ADM lies in its efficiency and reliability in solving nonlinear problems without requiring linearization. The obtained solutions are presented as polynomial approximations for each compartment in the model. MAPLE software is employed as the primary instrument to implement ADM and perform numerical simulations. The analysis includes examining the behaviour of susceptible, infected, treated, and recovered populations over time. The implications of this study suggest that ADM-based numerical approaches can be a valuable tool for policymakers and health practitioners in predicting disease dynamics and supporting the development of effective intervention strategies for Hepatitis B.